Taiwan, cambio político e identidad nacional - Herrera Feligreras, Andrés; Lu, Yu-Ting (Huarte de San Juan. Geografía e Historia, 2006)
After nearly fifty years of dictatorship, Taiwan celebrated, in March 1996, its first totally free elections. Celebration of these presidential elections meant the end of the political freedom process that had begun ten years before. The triumph was for the Koumintang, the party that had ruled the political, social and economical life of the isle since 1945. Kuomintang’s triumph, the party-estate that had driven, from its power situation, the way towards democracy, permitted to continue the political reform, but the great novelty appeared in the context of national identity. Debate about this issue was increasing its relevance –as a consequence of political steps taken by political power– until its key role in the present Taiwanese language situation. This article aims to examine, from a historical perspective, the construction of the present nationalist discourse in Taiwan as well as to examine the role of Kuomintang, from this perspective, during its first term of office (1996-2000) in democracy.